2012
DOI: 10.1007/s13205-012-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of melanin production by Brevundimonas sp. SGJ using response surface methodology

Abstract: Melanins are predominantly indolic polymers which are extensively synthesized in animals, plants and microorganisms. It has wide applications in cosmetics, agriculture and medicine. In the present study, optimization of process parameters influencing melanin production was attempted using the response surface methodology (RSM) from Brevundimonas sp. SGJ. A Plackett–Burman design was used for screening of critical components, while further optimization was carried out using the Box–Behnken design. The optimum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
4
50
0
Order By: Relevance
“…Melanin from Aeromonas sp. SNS was purified by previously described methods of Surwase et al and characterized using chemical and spectroscopic methods to confirm its identity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin from Aeromonas sp. SNS was purified by previously described methods of Surwase et al and characterized using chemical and spectroscopic methods to confirm its identity.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical characterization of melanin was carried out by testing its solubility in water, HCl, acetone, benzene, chloroform, ethanol, NaOH, and KOH. The specific chemical tests for melanin were carried out by adding the purified powder in H 2 O 2 , FeCl 3 , and KMnO 4 . The absorption spectra of extracted melanin (0.1 g L −1 ) were obtained by wavelength scanning from 200 to 800 nm by using a UV–Visible spectrophotometer (Shimadzu UV‐1800, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…SGJ, they conducted the response surface methodology (RSM) and determined the nutritional parameters influencing L-DOPA production: pH of 5.2, 1.55 g L −1 of tryptone, 4.21 g L −1 of L-tyrosine, and 0.037 g L −1 of CuSO 4 resulted in the highest L-DOPA production, 3.36 g L −1 . As a result, the optimized reaction media by RSM exhibited 8.36-fold increase in L-DOPA production and the highest tyrosinase activity was observed with 0.71 g L −1 of dry cell weight (Surwase et al 2012b). …”
Section: Based On Tyrosinase Activitymentioning
confidence: 91%
“…Shapes of the contour plots, circular or elliptical, emphasize the significant or insignificant interactions between the corresponding variables. Insignificant interactions amongst the corresponding variables were shown by circular contour plots while elliptical contour plots represent the significant interactions [14,32]. The response surface curves and contour plots rep resented in figure a 1 and b 1 show the interaction between gelatin and peptone.…”
Section: Collagenolytic Proteasementioning
confidence: 98%
“…Literature data showed that significant increase in product formation can be achieved by employing RSM [14][15][16]. Also some of the reports mentioned that use of more than one protein source is responsible for increase in protease yield [17,18].…”
mentioning
confidence: 99%